Transfer Teknologi Pemanfaatan Limbah Organik di Desa Baletbaru Areal Wilayah Pondok Pesantren Nurul Muhajirin Menjadi Pupuk Organik Cair dan Pupuk Organik Padat - Ummi - sholikhah (UII, 2019)
Abstract Baletbaru Village has several Islamic boarding schools, and this region has tremendous potential for community development activity to overcome problems that exist. Therefore, our partner in this training is one of the Islamic Boarding Schools in Baletbaru Village, Sukowono sub-district namely Islamic Boarding Schools Nurul Muhajirin. There are several problems that faced by partner, but many potentials are exist and have not been utilized. The main problem is the lack knowledge related to the utilization of organic waste as material for the production of liquid and solid organic fertilizers. Moreover, the knowledge related to the impact of excessive use of inorganic fertilizers is also lack, while Baletbaru village is very supportive for the use of organic waste become natural fertilizer can be used on agricultural land or inside boarding school are area. Based on this problems, the target of this Partnership Awarding Program (PPK) is to provide the education and training for the production of organic fertilizers by utilizing organic waste in the boarding school area. After this training, partner is expected to obtain the capability to apply the technology for liquid and solid organic fertilizer production that are environmentally friendly for agriculture. The community service activity has been significantly changed the knowledge and awareness of the community around Islamic boarding schools to the use of organic waste into organic fertilizer. Through this series of education and training, our activity partner is able to produce liquid and solid organic fertilizers using raw materials in the area of Islamic boarding schools.